2017
DOI: 10.1021/acsami.7b10641
|View full text |Cite
|
Sign up to set email alerts
|

Effective Trapping of Lithium Polysulfides Using a Functionalized Carbon Nanotube-Coated Separator for Lithium–Sulfur Cells with Enhanced Cycling Stability

Abstract: The critical issues that hinder the practical applications of lithium-sulfur batteries, such as dissolution and migration of lithium polysulfides, poor electronic conductivity of sulfur and its discharge products, and low loading of sulfur, have been addressed by designing a functional separator modified using hydroxyl-functionalized carbon nanotubes (CNTOH). Density functional theory calculations and experimental results demonstrate that the hydroxyl groups in the CNTOH provoked strong interaction with lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 69 publications
0
53
0
Order By: Relevance
“…To achieve efficient and working Li-S batteries, another nitrogen and sulfur co-doped porous carbon material was obtained from eggshell as starting material by Yuan et al [140] Ponraj et al reported the incorporation of MWCNTs partially functionalized with hydroxyl groups as a conductive coating on a commercial polyethylene separator (Asahi ND420). [141] Both theoretical predictions and experimental results affirmed the presence of a strong interaction between the hydroxyl groups and lithium polysulfides, effectively containing the polysulfides within the cathode side, while inherently conductive CNTs helped in the reutilization of active sulfur. SEM imaging revealed a tortuous intertwined morphology of the nanotubes both before and after functionalization with no visible change, while on the separator surface, the pore structure was not continuous.…”
Section: Heteroatom-doped Conductive Porous Carbon Materialsmentioning
confidence: 75%
See 1 more Smart Citation
“…To achieve efficient and working Li-S batteries, another nitrogen and sulfur co-doped porous carbon material was obtained from eggshell as starting material by Yuan et al [140] Ponraj et al reported the incorporation of MWCNTs partially functionalized with hydroxyl groups as a conductive coating on a commercial polyethylene separator (Asahi ND420). [141] Both theoretical predictions and experimental results affirmed the presence of a strong interaction between the hydroxyl groups and lithium polysulfides, effectively containing the polysulfides within the cathode side, while inherently conductive CNTs helped in the reutilization of active sulfur. SEM imaging revealed a tortuous intertwined morphology of the nanotubes both before and after functionalization with no visible change, while on the separator surface, the pore structure was not continuous.…”
Section: Heteroatom-doped Conductive Porous Carbon Materialsmentioning
confidence: 75%
“…Ponraj et al reported the incorporation of MWCNTs partially functionalized with hydroxyl groups as a conductive coating on a commercial polyethylene separator (Asahi ND420) . Both theoretical predictions and experimental results affirmed the presence of a strong interaction between the hydroxyl groups and lithium polysulfides, effectively containing the polysulfides within the cathode side, while inherently conductive CNTs helped in the reutilization of active sulfur.…”
Section: A Summary Of Recent Literature On Li‐s Battery Separators CLmentioning
confidence: 98%
“…The XPS spectrum of S 2p shows the presence of the polythionate and thiosulfate located at 169.5 and 168.4 eV, separately. The polythionate is formed by physical adsorption of polysulfides, while the formation of thiosulfate is attributed to the chemical bonding polysulfides with the hydroxyl group on rGO . Thus, it can be concluded that, after long‐term cycling, the polysulfides gradually localize at the rGO/CB (1:1) layer and stop them from passing through the separator to the lithium anode.…”
Section: Resultsmentioning
confidence: 99%
“…Surface functionalization, which generates surface functional groups on carbon materials, can enhance the trapping effect through chemical interactions with polysulfide species . Ponraj et al prepared a hydroxyl functionalized‐CNT (CNTOH)‐coated separator via a vacuum filtration method. The hydroxyl groups generate a strong interaction with lithium polysulfides on the CNTOH surface, which is indicated by the color change of the Li 2 S 4 solution (Figure A,C).…”
Section: Separators To Restrain Polysulfide Shuttle Effectmentioning
confidence: 99%
“…F, Theoretical binding energies for Li 2 S n intermediates on CNT and CNTOH. Reproduced with permission: Copyright 2017, American Chemical Society…”
Section: Separators To Restrain Polysulfide Shuttle Effectmentioning
confidence: 99%